Association of body mass index with morbidity following elective ventral hernia repair - Russyan Mark Mabeza, MD MPH; Nam Yong Cho, BS; Amulya Vadlakonda, BS; Sara Sakowitz, MS MPH; Shayan Ebrahimian, MS; Ashkan Moazzez, MD MPH; Peyman Benharash, MD MS (Surgery Open Science, 2023)
Background: Prior work has linked body mass index (BMI) with postoperative outcomes of ventral hernia repair (VHR), though recent data characterizing this association are limited. This study used a contemporary national cohort to investigate the association between BMI and VHR outcomes. Methods: Adults ≥ 18 years undergoing isolated, elective, primary VHR were identified using the 2016–2020 American College of Surgeons National Surgical Quality Improvement Program database. Patients were stratified by BMI. Restricted cubic splines were utilized to ascertain the BMI threshold for significantly increased morbidity. Multivariable models were developed to evaluate the association of BMI with outcomes of interest. Results: Of ~89,924 patients, 0.5 % were considered Underweight, 12.9 % Normal Weight, 29.5 % Overweight, 29.1 % Class I, 16.6 % Class II, 9.7 % Class III, and 1.7 % Superobese. After risk adjustment, class I (Adjusted Odds Ratio [AOR] 1.22, 95 % Confidence Interval [95%CI]: 1.06–1.41), class II (AOR 1.42, 95%CI: 1.21–1.66), class III obesity (AOR 1.76, 95%CI: 1.49–2.09) and superobesity (AOR 2.25, 95 % CI: 1.71–2.95) remained associated with increased odds of overall morbidity relative to normal BMI following open, but not laparoscopic, VHR. A BMI of 32 was identified as the threshold for the most significant increase in predicted rate of morbidity. Increasing BMI was linked to a stepwise rise in operative time and postoperative length of stay. Conclusion: BMI ≥ 32 is associated with greater morbidity following open, but not laparoscopic VHR. The relevance of BMI may be more pronounced in open VHR and must be considered for stratifying risk, improving outcomes, and optimizing care. Key message: Body mass index (BMI) continues to be a relevant factor in morbidity and resource use for elective open ventral hernia repair (VHR). A BMI of 32 serves as the threshold for significant increase in overall complications following open VHR, though this association is not observed in operations performed laparoscopically.